REVISITING A CULTURE OF TOLERANCE RELATING TO RELIGIOUS UNFAIR DISCRIMINATION IN SOUTH AFRICA (PART 2) - Radley Henrico (Obiter, 2017)
In Part 1 of this article the need to reconsider whether merely tolerating diversity in a multicultural and pluralistic secular South African society is sufficiently addressed. Transformative constitutionalism is the vanguard of ensuring a substantive change in our democratic order. Such change brought about as a result thereof would be meaningless if it failed to embrace the fact that the proverbial South African “rainbow nation” showcases an array of religions from various walks of life. Secularism, multicultural diversity and the necessity of having to live together are a reality, filled with the ever-present possibility of dispute, whether in civil society or the workplace. Ubuntu is instrumental to the success of transformative constitutionalism; especially when effect to its underlying principles is given impetus by the collective. This article is divided into two parts. In Part 1, tolerance was viewed in terms of the origin of the term; its meaning of forbearance and putting up with differences. The question was posed whether commitment to true democracy is not better aligned to the notion of celebration rather than toleration. This article looks at tolerance against the backdrop of Ubuntu and the imperative that we care for others not due to a sense of forbearance but rather through acclamation of a spirit of celebration of our differences. The case of City of Tshwane Metropolitan Municipality v Afriforum provides a crucial plank from which the notion of celebration, as opposed to mere toleration, should be embraced.